2023
DOI: 10.3390/dj11060141
|View full text |Cite
|
Sign up to set email alerts
|

Association between Malnutrition and Dental Caries in Iraqi Kurdish Children

Abstract: Background: This paper aimed to study the association of serum Vitamin D level and Body Mass Index (BMI) as representatives of malnutrition at micro and macro levels, respectively, on dental caries. Method and Participants: A total of 333 randomly selected children aged 6–12 years in Sulaimani, Kurdistan, Iraq were examined for three variables of the Decayed Missed Filled Tooth (DMFT) index, BMI, and Vitamin D serum levels in a single-time cross-sectional snapshot. Results: The majority of the population studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Numerous epidemiological studies have suggested a possible connection between vitamin D levels in the general population and the development of dental caries [9,[26][27][28]. Nevertheless, current research evidence remains inconclusive in establishing a definitive relationship [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous epidemiological studies have suggested a possible connection between vitamin D levels in the general population and the development of dental caries [9,[26][27][28]. Nevertheless, current research evidence remains inconclusive in establishing a definitive relationship [29,30].…”
Section: Introductionmentioning
confidence: 99%